Advances in Use of Nanomaterials for Musculoskeletal Regeneration - Josef Jampilek; Daniela Placha (MDPI AG, 2021)
Since the worldwide incidence of bone disorders and cartilage damage has been increasing and traditional therapy has reached its limits, nanomaterials can provide a new strategy in the regeneration of bones and cartilage. The nanoscale modifies the properties of materials, and many of the recently prepared nanocomposites can be used in tissue engineering as scaffolds for the development of biomimetic materials involved in the repair and healing of damaged tissues and organs. In addition, some nanomaterials represent a noteworthy alternative for treatment and alleviating inflammation or infections caused by microbial pathogens. On the other hand, some nanomaterials induce inflammation processes, especially by the generation of reactive oxygen species. Therefore, it is necessary to know and understand their effects in living systems and use surface modifications to prevent these negative effects. This contribution is focused on nanostructured scaffolds, providing a closer structural support approximation to native tissue architecture for cells and regulating cell proliferation, differentiation, and migration, which results in cartilage and bone healing and regeneration.